Difference between revisions of "009B Sample Final 1, Problem 6"
Jump to navigation
Jump to search
(Created page with "<span class="exam"> Evaluate the improper integrals: ::<span class="exam">a) <math>\int_0^{\infty} xe^{-x}~dx</math> ::<span class="exam">b) <math>\int_1^4 \frac{dx}{\sqrt{4-...") |
|||
(3 intermediate revisions by the same user not shown) | |||
Line 1: | Line 1: | ||
<span class="exam"> Evaluate the improper integrals: | <span class="exam"> Evaluate the improper integrals: | ||
− | + | <span class="exam">(a) <math>\int_0^{\infty} xe^{-x}~dx</math> | |
− | + | ||
+ | <span class="exam">(b) <math>\int_1^4 \frac{dx}{\sqrt{4-x}}</math> | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Foundations: | !Foundations: | ||
|- | |- | ||
− | |'''1.''' How could you write <math style="vertical-align: -14px">\int_0^{\infty} f(x)~dx</math> so that you can integrate? | + | |'''1.''' How could you write <math style="vertical-align: -14px">\int_0^{\infty} f(x)~dx</math> so that you can integrate? |
|- | |- | ||
| | | | ||
− | + | You can write <math>\int_0^{\infty} f(x)~dx=\lim_{a\rightarrow\infty} \int_0^a f(x)~dx.</math> | |
|- | |- | ||
− | |'''2.''' How could you write <math>\int_{-1}^1 \frac{1}{x}~dx</math> | + | |'''2.''' How could you write <math>\int_{-1}^1 \frac{1}{x}~dx?</math> |
|- | |- | ||
| | | | ||
− | + | The problem is that <math>\frac{1}{x}</math> is not continuous at <math style="vertical-align: 0px">x=0.</math> | |
|- | |- | ||
| | | | ||
− | + | So, you can write <math style="vertical-align: -15px">\int_{-1}^1 \frac{1}{x}~dx=\lim_{a\rightarrow 0^-} \int_{-1}^a \frac{1}{x}~dx+\lim_{a\rightarrow 0^+} \int_a^1 \frac{1}{x}~dx.</math> | |
|- | |- | ||
− | |'''3.''' How would you integrate <math style="vertical-align: -13px">\int xe^x\,dx</math> | + | |'''3.''' How would you integrate <math style="vertical-align: -13px">\int xe^x\,dx?</math> |
|- | |- | ||
| | | | ||
− | + | You can use integration by parts. | |
|- | |- | ||
| | | | ||
− | + | Let <math style="vertical-align: 0px">u=x</math> and <math style="vertical-align: 0px">dv=e^xdx.</math> | |
|} | |} | ||
+ | |||
'''Solution:''' | '''Solution:''' | ||
Line 36: | Line 38: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |First, we write <math style="vertical-align: -14px">\int_0^{\infty} xe^{-x}~dx=\lim_{a\rightarrow \infty} \int_0^a xe^{-x}~dx</math> | + | |First, we write <math style="vertical-align: -14px">\int_0^{\infty} xe^{-x}~dx=\lim_{a\rightarrow \infty} \int_0^a xe^{-x}~dx.</math> |
|- | |- | ||
− | |Now, we proceed using integration by parts. Let <math style="vertical-align: 0px">u=x</math> and <math style="vertical-align: 0px">dv=e^{-x}dx</math> | + | |Now, we proceed using integration by parts. |
+ | |- | ||
+ | |Let <math style="vertical-align: 0px">u=x</math> and <math style="vertical-align: 0px">dv=e^{-x}dx.</math> | ||
+ | |- | ||
+ | |Then, <math style="vertical-align: 0px">du=dx</math> and <math style="vertical-align: 0px">v=-e^{-x}.</math> | ||
|- | |- | ||
|Thus, the integral becomes | |Thus, the integral becomes | ||
|- | |- | ||
| | | | ||
− | + | <math>\int_0^{\infty} xe^{-x}~dx=\lim_{a\rightarrow \infty} \left.-xe^{-x}\right|_0^a-\int_0^a-e^{-x}\,dx.</math> | |
|} | |} | ||
Line 49: | Line 55: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |For the remaining integral, we need to use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: 0px">u=-x</math> | + | |For the remaining integral, we need to use <math style="vertical-align: 0px">u</math>-substitution. |
+ | |- | ||
+ | |Let <math style="vertical-align: 0px">u=-x.</math> Then, <math style="vertical-align: 0px">du=-dx.</math> | ||
|- | |- | ||
|Since the integral is a definite integral, we need to change the bounds of integration. | |Since the integral is a definite integral, we need to change the bounds of integration. | ||
|- | |- | ||
− | |Plugging in our values into the equation <math style="vertical-align: | + | |Plugging in our values into the equation <math style="vertical-align: -4px">u=-x,</math> we get |
+ | |- | ||
+ | | <math style="vertical-align: -5px">u_1=0</math> and <math style="vertical-align: -3px">u_2=-a.</math> | ||
|- | |- | ||
|Thus, the integral becomes | |Thus, the integral becomes | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\int_0^{\infty} xe^{-x}~dx} & = & \displaystyle{\lim_{a\rightarrow \infty} -xe^{-x}\bigg|_0^a-\int_0^{-a}e^{u}~du}\\ | \displaystyle{\int_0^{\infty} xe^{-x}~dx} & = & \displaystyle{\lim_{a\rightarrow \infty} -xe^{-x}\bigg|_0^a-\int_0^{-a}e^{u}~du}\\ | ||
&&\\ | &&\\ | ||
Line 73: | Line 83: | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\int_0^{\infty} xe^{-x}~dx} & = & \displaystyle{\lim_{a\rightarrow \infty} -ae^{-a}-(e^{-a}-1)}\\ | \displaystyle{\int_0^{\infty} xe^{-x}~dx} & = & \displaystyle{\lim_{a\rightarrow \infty} -ae^{-a}-(e^{-a}-1)}\\ | ||
&&\\ | &&\\ | ||
Line 84: | Line 94: | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\int_0^{\infty} xe^{-x}~dx} & = & \displaystyle{\lim_{a\rightarrow \infty} \frac{-1}{e^a}+1}\\ | \displaystyle{\int_0^{\infty} xe^{-x}~dx} & = & \displaystyle{\lim_{a\rightarrow \infty} \frac{-1}{e^a}+1}\\ | ||
&&\\ | &&\\ | ||
Line 100: | Line 110: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |First, we write <math>\int_1^4 \frac{dx}{\sqrt{4-x}}=\lim_{a\rightarrow 4} \int_1^a\frac{dx}{\sqrt{4-x}}</math>. | + | |First, we write <math>\int_1^4 \frac{dx}{\sqrt{4-x}}=\lim_{a\rightarrow 4^-} \int_1^a\frac{dx}{\sqrt{4-x}}.</math> |
+ | |- | ||
+ | |Now, we proceed by <math style="vertical-align: 0px">u</math>-substitution. | ||
|- | |- | ||
− | | | + | |We let <math style="vertical-align: -1px">u=4-x.</math> Then, <math style="vertical-align: 0px">du=-dx.</math> |
|- | |- | ||
|Since the integral is a definite integral, we need to change the bounds of integration. | |Since the integral is a definite integral, we need to change the bounds of integration. | ||
|- | |- | ||
− | |Plugging in our values into the equation <math style="vertical-align: - | + | |Plugging in our values into the equation <math style="vertical-align: -4px">u=4-x,</math> we get |
+ | |- | ||
+ | | <math style="vertical-align: -5px">u_1=4-1=3</math> and <math style="vertical-align: -3px">u_2=4-a.</math> | ||
|- | |- | ||
|Thus, the integral becomes | |Thus, the integral becomes | ||
|- | |- | ||
| | | | ||
− | + | <math>\int_1^4 \frac{dx}{\sqrt{4-x}}\,=\,\lim_{a\rightarrow 4^-} \int_3^{4-a}\frac{-1}{\sqrt{u}}~du.</math> | |
|} | |} | ||
Line 120: | Line 134: | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
− | \displaystyle{\int_1^4 \frac{dx}{\sqrt{4-x}}} & = & \displaystyle{\lim_{a\rightarrow 4} -2u^{\frac{1}{2}}\bigg|_{3}^{4-a}}\\ | + | \displaystyle{\int_1^4 \frac{dx}{\sqrt{4-x}}} & = & \displaystyle{\lim_{a\rightarrow 4^-} -2u^{\frac{1}{2}}\bigg|_{3}^{4-a}}\\ |
&&\\ | &&\\ | ||
− | & = & \displaystyle{\lim_{a\rightarrow 4}-2\sqrt{4-a}+2\sqrt{3}}\\ | + | & = & \displaystyle{\lim_{a\rightarrow 4^-}-2\sqrt{4-a}+2\sqrt{3}}\\ |
&&\\ | &&\\ | ||
& = & \displaystyle{2\sqrt{3}}.\\ | & = & \displaystyle{2\sqrt{3}}.\\ | ||
\end{array}</math> | \end{array}</math> | ||
|} | |} | ||
+ | |||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Final Answer: | !Final Answer: | ||
|- | |- | ||
− | |'''(a)''' <math style="vertical-align: -3px">1</math> | + | | '''(a)''' <math style="vertical-align: -3px">1</math> |
|- | |- | ||
− | |'''(b)''' <math style="vertical-align: -4px">2\sqrt{3}</math> | + | | '''(b)''' <math style="vertical-align: -4px">2\sqrt{3}</math> |
|} | |} | ||
[[009B_Sample_Final_1|'''<u>Return to Sample Exam</u>''']] | [[009B_Sample_Final_1|'''<u>Return to Sample Exam</u>''']] |
Latest revision as of 17:06, 20 May 2017
Evaluate the improper integrals:
(a)
(b)
Foundations: |
---|
1. How could you write so that you can integrate? |
You can write |
2. How could you write |
The problem is that is not continuous at |
So, you can write |
3. How would you integrate |
You can use integration by parts. |
Let and |
Solution:
(a)
Step 1: |
---|
First, we write |
Now, we proceed using integration by parts. |
Let and |
Then, and |
Thus, the integral becomes |
|
Step 2: |
---|
For the remaining integral, we need to use -substitution. |
Let Then, |
Since the integral is a definite integral, we need to change the bounds of integration. |
Plugging in our values into the equation we get |
and |
Thus, the integral becomes |
|
Step 3: |
---|
Now, we evaluate to get |
|
Using L'Hôpital's Rule, we get |
|
(b)
Step 1: |
---|
First, we write |
Now, we proceed by -substitution. |
We let Then, |
Since the integral is a definite integral, we need to change the bounds of integration. |
Plugging in our values into the equation we get |
and |
Thus, the integral becomes |
|
Step 2: |
---|
We integrate to get |
|
Final Answer: |
---|
(a) |
(b) |